Pergolide Mesilate May Improve Fatigue in Patients with Parkinson’s Disease - Kazuo Abe; Mayako Takanashi; Takehiko Yanagihara; Sabro Sakoda (Behavioural Neurology)
Objectives: Fatigue is a complaint frequently encountered among patients with Parkinson’s disease (PD). Considering the possible relationship between fatigue and dopaminergic dysfuncion, we investigated the effect of pergolide mesilate (a D2 and D1 dopamine receptor agonist) and bromocriptine (a D2 selective dopamine receptor) in patients with PD.